The Effect Of Competence On The Performance Of Middle And High School Teachers At Cita Hati Schools In Surabaya - Yeremia Chrisbiyanto; Daniel Ari Wibowo; Agustinus Foat (Jurnal Didaskalia, 2022)
This study aims to determine the effect of (1) pedagogical competence, (2) professional competence, (3) social competence, and (4) teacher personality competence simultaneously on the performance of Middle and High school Cita Hati Surabaya teachers. The type of research used is quantitative research. The research subjects were all teachers of Middle and High school Cita Hati Surabaya with a total of 120 teachers, and the object of this research was teacher competence and teacher performance. Data were collected using a questionnaire, and analyzed by 'ryx' test, F test, and linear regression analysis. The results showed that there was a relationship between the competency variable (X) and the performance variable for junior-senior high school teachers at Cita Hati Surabaya School (Y) with a ryx value of 0.701 and a positive value. There is a significant relationship between the competency variable (X) in shaping the teacher performance variable for Middle and High school at Cita Hati Surabaya School (Y) with an F value of 72,343 with a value of = 0.00 which is significant at < 0.05. The equation of the linear regression line is = 18.534 + 0.742 X. This means that for every improvement in competence once, the performance of Middle and High school teachers at Cita Hati Schools in Surabaya is 0.742 times.